Relative validity and reproducibility of a semi-quantitative food frequency questionnaire to assess fruit and vegetable consumption in school-aged children - Ilić, Ana; Rumbak, Ivana; Brečić, Ružica; Colić Barić, Irena; Bituh, Martina (Frontiers in Nutrition, 2022)
Since the beneficial effects of fruit and vegetable (FV) consumption on health are well known due to the synergy of their nutrients and non-nutrients, it is crucial to have good tools to assess FV intake. A food frequency questionnaire (FFQ) is an adequate method to estimate FV consumption, but it is necessary to relate this dietary method to the geographic and cultural environment. Therefore, this study presented the development of the semi-quantitative FFQ to estimate FV intake in school-aged children that usually consume cooked homemade and schools’ meals. It also aimed to evaluate the relative validity and reproducibility of the FFQ. School-aged children (baseline age 8 years) from 14 primary schools in the city of Zagreb participated in the study during the 2019/2020 school year. Parents/caregivers, together with the children, completed the FFQs and 3-day dietary records (3DDR). The FFQ was designed to assess consumption of 8 food categories. The FFQ was validated using the 3DDR of 141 children (51.4% of boys), whereas the reproducibility test included the FFQs of 161 children (53.4% of boys). Of 8 food categories, FFQ overestimates consumption of 3 and underestimates of 3 food categories (p < 0.05; Wilcoxon signed rank test) compared to 3DDR. De-attenuated correlation coefficients estimated a good to moderate relationship (0.217 - 0.384) between FFQ and 3DDR. Cross-classification analysis revealed that overall 28-41% of children were classified in the same quartile, whereas less than 10% of children were extremely misclassified for all food categories obtained from 3DDR and FFQ1. The κw-values showed fair agreement for all food categories. Bland-Altman analysis results showed relatively small bias for all food categories (median between -11.7 g and -54.8 g) with no systematic patterns between FFQ and 3DDR. No differences were found between food categories estimated with the FFQs on both occasion, and Spearman correlation coefficients ranged from 0.664 to 0.712 (p < 0.01). The Cronbach's alpha values (α > 0.700) and ICCs (range 0.724 - 0.826; p < 0.01) indicate good reproducibility of the FFQ. The results indicate reasonable relative validity and acceptable reproducibility of the FFQ for estimating FV consumption among school-aged children.